THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE ON BANKING COMPANY VALUE BEFORE AND DURING COVID-19 - Sri Mulyati; Putri Rizki Syafitri; Bambang Sugiharto (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This research was conducted to determine the effect of sustainability report disclosure on company value before and during the Covid-19 pandemic. In this study a descriptive verification research method was used, with quantitative data types, using secondary data sources, populations and samples of banking sector companies that issue sustainability reports listed on the Indonesian Stock Exchange. The sampling technique used is non-probability sampling and the determination of the sample uses purposive sampling. The method used in this study is using the panel data regression method with the help of the Eviews application software. The results of the study show that the hypothesis test is acceptable, because there are differences in the effect of the Sustainability Report Disclosure before and during Covid-19 on company value. Where research conducted in the before covid-19 period showed the result that Sustainability Report Disclosure had an influence on company value, while the period during covid-19 did not affect the company’s value.